Dyschromonychia: clinical significance in a South African population - P.F. Levay; M.E. Botes; E. Malela (South African Family Practice)
Background: The purpose of this study was to determine disease associations with dyschromonychia (DCO) in an out- and inpatient population attending Kalafong Hospital.